Electrocardiographic Responses During Fire Suppression and Recovery Among Experienced Firefighters. Issue 9 (September 2015) - Al-Zaiti, Salah; Rittenberger, Jon C.; Reis, Steven E.; Hostler, David
Abstract : Objective: We sought to evaluate the impact of high-intensity exertion and heat stress on electrocardiographic changes during fire suppression and recovery. Methods: Healthy firefighters completed a live-fire training evolution. Each firefighter was randomly assigned to complete either two or three intervals of fire suppression tasks followed by a structured recovery. Firefighters were continuously monitored using 12-lead Holter electrocardiogram. Results: Most firefighters (71.4%) exceeded their maximum heart rate and one third had pathological ST events. Nearly one third of each of these abnormalities persisted throughout recovery period. Longer fire suppression intervals did not affect the incidence of these abnormalities. Conclusions: Fire suppression is associated with ST-segment changes among firefighters at low risk for cardiovascular disease. These abnormalities continued into initial recovery even though cooling and rehydration were provided.